Clinical Subtyping of Ménière's Disease. (24th April 2018) - Phillips, John S.; Murdin, Louisa; Rea, Peter; Sutton, Liam
Abstract : Fundamentally, Ménière's disease is a constellation of symptoms and, as such, may represent the final common pathway for a number of disease processes, as opposed to being the consequence of a single isolated pathology. Within this type of consideration, much can be learned regarding the etiology, presentation, prognosis, and treatment of these individual conditions by applying subtyping techniques currently employed to better understand similar disease processes that are encountered in other allied fields of medicine. This commentary proposes the principles, required processes, and benefits of subtyping for Ménière's disease.